The Behaviour and Influence Mechanism of the Subject of IUR Collaborative Innovation: A Simulation Study Based on NetLogo - Yanrong Wang; Xiaochao Yao; Lei Song; Shujing Zhang (Discrete Dynamics in Nature and Society)
This paper simulates the behavior mechanism of each subject in the equipment manufacturing industry-university-research (IUR) collaborative innovation system based on NetLogo, and constructs the input-output model of each subject. Secondly, the reasonable value of each parameter is determined through expert consultation, and finally 6 scenarios are selected to simulate the evolution of the IUR collaborative innovation system. The results show that different decision-making behaviors of each subject will lead to different operating states of the innovation collaborative system. When the conditions of each subject are exactly the same, the innovation system can achieve stable and continuous operation. However, if the initial conditions are different, the IUR collaborative innovation system needs an authoritative intermediary to coordinate the behavioral strategies of each subject, strengthen the willingness to cooperate, and ensure its stable operation. Reasonable reward and punishment measures are also an effective and important measure, which can mobilize the enthusiasm of all subjects for collaborative innovation. This paper is of great significance for the IUR collaborative innovation in equipment manufacturing industry.